2011
DOI: 10.1097/prs.0b013e318205f36f
|View full text |Cite
|
Sign up to set email alerts
|

The Keystone Island Flap: Use in Large Defects of the Trunk and Extremities in Soft-Tissue Reconstruction

Abstract: The keystone flap can be applied to large defects of the trunk and extremities, obviating the need for either microsurgical techniques or extensive operative time while achieving primary wound healing. Despite minor complications, the 97 percent reconstructive success rate compares well to published rates of microsurgical tissue transfers but has several advantages: short operative times, high reproducibility, ease of use, and favorable aesthetic outcome. The authors conclude that the keystone flap is a reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 15 publications
2
87
1
3
Order By: Relevance
“…28 Previous modifications include a "yin yang" reconstruction, 29 including partial undermining and interdigitation of bilateral keystone flaps, 7 and the "omega variant," where both limbs of a single keystone are folded into a horseshoe shape. 30 Although there is a significant reduction in flap loss and partial necrosis, these complications may still occur 10,21,26 ; however, most can be treated conservatively or with minor intervention. A comparison with other sarcoma flap reconstructions at the Mayo Clinic over the past 5 years (n = 127 patients) shows that 9 percent were free flaps and the remainder were locoregional pedicled flaps.…”
Section: Key Points Of Flap Harvest Potential Advantagesmentioning
confidence: 97%
See 1 more Smart Citation
“…28 Previous modifications include a "yin yang" reconstruction, 29 including partial undermining and interdigitation of bilateral keystone flaps, 7 and the "omega variant," where both limbs of a single keystone are folded into a horseshoe shape. 30 Although there is a significant reduction in flap loss and partial necrosis, these complications may still occur 10,21,26 ; however, most can be treated conservatively or with minor intervention. A comparison with other sarcoma flap reconstructions at the Mayo Clinic over the past 5 years (n = 127 patients) shows that 9 percent were free flaps and the remainder were locoregional pedicled flaps.…”
Section: Key Points Of Flap Harvest Potential Advantagesmentioning
confidence: 97%
“…These flaps are executed as a single multiperforator fasciocutaneous advancement flap based on random fasciocutaneous or musculocutaneous perforators. 10 Principles in vascular anatomy and perforator vascular territories (perforasome) 2 can be used to reappraise the vascular basis of the keystone flap and modifications of the flap design to maintain vascular integrity.…”
Section: Plastic and Reconstructive Surgery • June 2016mentioning
confidence: 99%
“…6 Khouri et al reported a 35.7% complication rate in a cohort of 28 patients with a keystone flap for a large soft tissue defect to the trunk and extremities but only 2 patients had partial flap necrosis and 1 required a skin graft for wound closure. 7 In our case, with potentially difficult and challenging anatomical territory, we achieved a stable, durable, excellent aesthetic and sensate reconstruction. We used a unilateral keystone flap for perianal soft tissue reconstruction.…”
Section: Discussionmentioning
confidence: 91%
“…The flap is designed as a large 3:1 ellipse parallel to the long axis of the defect. 2 The blood supply to the flap is based on cutaneous perforators that shift toward the defect when the flap is advanced. Once the leading edge of the keystone flap is inset the donor site is closed on itself from the poles of the long axis of the flap to the side of the flap remote from the defect.…”
Section: Local Flap Optionsmentioning
confidence: 99%